Manufacture of Lithium Lanthanum Titanate Active Material as a Lithium-Ion Capacitor Anode Using Solid-State Reaction Methods - Liza, Erliza Pratiwi; Humaidi, Syahrul; Rifai, Abdulloh (Journal of Technomaterial Physics, 2023)
Lithium lanthanum titanate, Li0.2La0.6TiO3 (LLTO) was synthesized for the manufacture of lithium-ion capacitors using the solid-state reaction method. in this study, the active ingredients were synthesized using variations of lithium and lanthanum as raw materials. The raw materials used are Li2CO3, La2O3, and TiO2. The three raw materials were mixed according to the stoichiometric calculations then added 13 ml of Ethanol solution so that the raw materials were mixed evenly during the milling process for 5 hours. Sintering was carried out for 8 hours at 800oC and then at 1150oC for 12 hours. The sintered powder was ground using a mortar and pastel and then sieved on a 400 mesh sieve. The anode sheet was made by mixing the active ingredients: PVDF: Super-P with a composition of 85:10:5 by adding 3 ml of DMAC solvents. The characterization test was carried out using XRD while the electrochemical test used CV and EIS. The XRD result shows the formation of the main phase and the impurity phase with the main phase percent of 96.4%. From the results of electrochemical testing, the percentage of capacity is 73%.